2022
DOI: 10.1590/1807-1929/agriambi.v26n3p173-179
|View full text |Cite
|
Sign up to set email alerts
|

Green and sweet corn grown under different cover crops and phases of the no-tillage system

Abstract: Special corn is cultivated all year conventionally round; however, its productivity increases when grown under a no-tillage system (NTS). This study aimed to evaluate the agronomic performance of sweet and green corn cultivated under residues of different cover crops and the NTS implantation stages. Two experiments were carried out in the randomized block design, with four replications, in each of the three areas. The experiments consisted of evaluating the sweet and green corn, simultaneously, in three areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…30 days after cutting the green manures (DACGM) [2], maize was sown. Crop Top 520 hybrid maize was planted with a planting density of 0.50 m between rows and 0.30 m between plants at a depth of 2 cm [22]. Two seeds were planted in each hole, and planting was carried out manually using a seed drill.…”
Section: Installation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…30 days after cutting the green manures (DACGM) [2], maize was sown. Crop Top 520 hybrid maize was planted with a planting density of 0.50 m between rows and 0.30 m between plants at a depth of 2 cm [22]. Two seeds were planted in each hole, and planting was carried out manually using a seed drill.…”
Section: Installation Processmentioning
confidence: 99%
“…Similar results were observed in the present study. Nunes et al [22] planted maize after cover crops in no-tillage conditions. Tey observed that when dry matter of the soil cover increased, maize yield also increased.…”
Section: Plant Height Stalk Diameter Number Of Grains Per Row Number ...mentioning
confidence: 99%
“…Grains are consumed in their fresh form and processed foods, such as flaked flour, corn starch, and canned corn, but also in animal feed (Giordano et al, 2018), in the production of forage, energy, and industrial materials (Guo et al, 2018). However, there is no official record of green corn in Brazil, however, it is known that in 2018 world production was 9.1 million tons with an average yield of 8.1 Mg ha -1 (Nunes et al, 2022).…”
Section: Introductionmentioning
confidence: 99%